1998
DOI: 10.3122/15572625-11-1-23
|View full text |Cite
|
Sign up to set email alerts
|

New-Patient Self-History Questionnaires in Primary Care

Abstract: Background: In the current environment of increasing health care efficiency, the benefits of patient selfhistory questionnaires need to be fully explored. The utility and reliability of new-patient self-history questionnaires have been documented in the medical literature. This study investigates the prevalence of these patient self-history forms in primary care offices.Methods: A sample of primary care offices listed in the yellow pages by specialty were surveyed by telephone. Survey questions included the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In the primary care setting, a recent survey of 116 offices and 400 physicians in Chicago found that only 53% of practices used paper questionnaires despite their proven advantages. 47 Guthmann 47 wrote:…”
Section: Patient Questionnaires: Adding Structure To the Interviewmentioning
confidence: 99%
“…In the primary care setting, a recent survey of 116 offices and 400 physicians in Chicago found that only 53% of practices used paper questionnaires despite their proven advantages. 47 Guthmann 47 wrote:…”
Section: Patient Questionnaires: Adding Structure To the Interviewmentioning
confidence: 99%
“…On the other hand, Pecoraro shown that self HT and clinical HT requires similar time, while Maultsby and Rockart reported conflicting results, with some advantage to reduction of time spent [23,30,58]. Other authors only supposes that the previous use of a HTI will reduce consultation time, or provide information at no clinician time expense, but did not provide any empirical evidence [4,9,52,55,[61][62][63]65,66,10,11,16,42,[45][46][47]49]. Beyond that, the benefits for clinician and patients of a time saving routine were not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the benefits for practice, efficiency, and diagnosis shown by these HTI, their use still not widespread. By the end of the nineties, HTIs were not clinically used in US [45]. A review about computer HT, [46] tried to answer its limits: the contributions were not considered decisive for clinicians, have low specificity, and raise issues to clinician workflow [46].…”
Section: The 1990s and 2000smentioning
confidence: 99%
“…However, resources are scarce. Pre‐interview patient questionnaires (often not validated) are a common method of collecting data before the consultation (3). However, findings of whether taboo subjects are underreported in questionnaires have been contradictory (4, 10).…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaires are internationally used in manypractices and hospitals (3). In Sweden, with a present population of 8.86 million people, a register was started in 1996 to quality assess uterine surgery for benign disorders.…”
Section: Introductionmentioning
confidence: 99%